Efficacy of buccal piroxicam infiltration and inferior alveolar nerve block in patients with irreversible pulpitis: a prospective, double-blind, randomized clinical trial - Saurav Paul; Sridevi Nandamuri; Aakrati Raina; Mukta Bansal (Restorative Dentistry & Endodontics, 2021)
ObjectivesThis randomized clinical trial aimed to assess the effectiveness of buccal infiltration with piroxicam on the anesthetic efficacy of inferior alveolar nerve block (IANB) with buccal infiltration in irreversible pulpitis, with pain assessed using the Heft-Parker visual analogue scale (HP-VAS).Materials and MethodsThis study included 56 patients with irreversible pulpitis in mandibular molars, randomly distributed between 2 groups (n = 28). After evaluating the initial pain score with the HP-VAS, each patient received IANB followed by buccal infiltration of 2% lignocaine with adrenaline (1:80,000). Five minutes later, the patients in groups 1 and 2 were given buccal infiltration with 40 mg/2 mL of piroxicam or normal saline, respectively. An access opening procedure (AOP) was performed 15 minutes post-IANB once the individual showed signs of lip numbness as well as 2 negative responses to electric pulp testing. The HP-VAS was used to grade the patient's pain during caries removal (CR), AOP, and working length measurement (WLM). Successful anesthesia was identified either by the absence of pain or slight pain through CR, AOP, and WLM, with no requirement of a further anesthetic dose. A statistical analysis was done using the Shapiro-Wilk and Mann-Whitney U tests.ResultsThe piroxicam group presented a significantly lower (p < 0.05) mean pain score than the saline group during AOP.ConclusionsBuccal infiltration with piroxicam enhanced the efficacy of anesthesia with IANB and buccal infiltration with lignocaine in patients with irreversible pulpitis.